Teaching architecture in the age of a fragile humanity (EAAE Annual Conference Proceedings, 2023)
Thinking about the meaning of education in architecture requires a reflection on the contemporary world as a subject and object of design. The capitalist development of construction and real estate has meant that today only an insignificant number of constructed buildings are designed by architects.